A good day to pie - Popp, Misha (Popp, Misha. Pies before guys mystery., 2023)
"Daisy bakes a little murder into every pie she creates, and she and her dog, Zoe, deliver them to the town's worst cads. Now, Daisy's entered a televised, elimination-style competition and has a shot at $100k in prize money--but she still has a murder pie to deliver between filming. In a completely unexpected turn of events, she discovers that her intended victim is one of the competition judges, and he turns up dead before the pie even arrives. Now, Daisy has to solve the murder--even if it means working a bit of magic--before someone calls foul play and exposes her murderous secret. For anyone who's ever fantasized about the world of competitive baking à la the Great British Bake Off--or has ever dreamed of getting back at that guy who wronged them years ago--Popp's culinary cozy series is as alluring as a perfectly baked pie, this edgy yet utterly charming novel takes the idea of "a dessert to die for" to a whole new level."--